2020
DOI: 10.1177/1947603520905113
|View full text |Cite
|
Sign up to set email alerts
|

Severe Acute Localized Reactions Following Intra-Articular Hyaluronic Acid Injections in Knee Osteoarthritis

Abstract: Objective Concerns have been raised about severe acute localized reactions (SALR) following intra-articular (IA) hyaluronic acid (HA) injections for knee osteoarthritis (OA). We compared surrogate SALR measures between hylan G-F 20 and non-hylan G-F 20 HA patients and evaluated corresponding SALR risk factors for hylan G-F 20 patients. Design Knee OA patients were identified from the Optum Clinformatics dataset (January 2006 to June 2016), stratified into hylan G-F 20 and non-hylan G-F 20 HA users. Occurrences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 25 publications
0
9
0
2
Order By: Relevance
“…Previously published findings from the same database as the present study showed that there was no statistically significant difference in SALRs between hylan and non-hylan G-F 20 products. 25 Those findings suggested that crosslinking or avian-derived HA may not play a role in SALRs as had been previously hypothesized, but the analysis was not stratified to be able to provide further comparisons of different products.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Previously published findings from the same database as the present study showed that there was no statistically significant difference in SALRs between hylan and non-hylan G-F 20 products. 25 Those findings suggested that crosslinking or avian-derived HA may not play a role in SALRs as had been previously hypothesized, but the analysis was not stratified to be able to provide further comparisons of different products.…”
Section: Discussionmentioning
confidence: 94%
“…In claims database study of almost 750,000 HA patients, the diagnosis of inflammation or infection within 3 days of a HA injection was extremely rare for both hylan G-F 20 (0.001%) and non-hylan G-F 20 (0.002%) HA patients. 25 The study also concluded that the overall risk of surrogate severe acute localized reaction measures was similar for hylan G-F 20 and non-hylan G-F 20 HA patients. However, the non-hylan G-F 20 HA group was not stratified based on the specific HA product that was used, thus not allowing any further comparisons with hylan G-F 20.…”
Section: Introductionmentioning
confidence: 86%
“…10,29) It is suspected that chemically cross-linked HA molecules are the cause of arthritis 36) or that the accumulation of HA results in sensitization 37) ; nonetheless, there are reports that these reactions can occur after the first HA injection 38) or after injection of HAs other than Hylan G-F 20, and the cause of this has not yet been clarified. 39) Considering these reports, it is considered that Hylan G-F 20 can be used safely, but it must be used with caution because any acute inflammatory reaction may require differentiation from septic arthritis. Data from the national registry of Iceland indicate that the infection rate after hip injection is estimated to be 0.037%.…”
Section: Discussionmentioning
confidence: 99%
“…However, some allergic side effects have been seen in HA injection related to the origin of this product (animal derived glycosaminoglycan, such as cockscomb tissue). Pain and swelling after injection could be related to the high molecular weight and different pharmaceutical formulations of HA [60]. The other major challenge of treatment with HA is the multiple injection requirement in order to get to the desired efficiency.…”
Section: Pharmacological Treatmentsmentioning
confidence: 99%